CLASSIFICATION OF PHRASEOLOGICAL UNITS OF THE KOREAN LANGUAGE BY SYNTACTIC STRUCTURE (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
It is well known that phraseological units are one of the most complex and multifaceted categories of linguistics, which, in turn, is characterized by stability, semantic integrity and the impossibility of arbitrary replacement of components. In this context, it is important to emphasize that the study of the syntactic structure of phraseological units allows not only to identify their formal-grammatical organization, but also, which is important, to determine the features of the semantic connection between the constituent elements.